# |
ODE |
Mathematica |
Maple |
\[
{}3 x -y+1-\left (6 x -2 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -2 y-3+\left (2 x +y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}10 x -4 y+12-\left (x +5 y+3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}6 x +4 y+1+\left (4 x +2 y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x -y-6+\left (x +y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+1+\left (4 x +6 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x +3 y+1+\left (x +y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \sin \left (t \right )+\cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x^{2}-1}
\] |
✓ |
✓ |
|
\[
{}u^{\prime } = 4 t \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}z^{\prime } = x \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}T^{\prime } = {\mathrm e}^{-t} \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \sec \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -\frac {1}{3} x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 2 \sin \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x V^{\prime } = x^{2}+1
\] |
✓ |
✓ |
|
\[
{}x^{\prime } {\mathrm e}^{3 t}+3 x \,{\mathrm e}^{3 t} = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -x+1
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x \left (2-x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \left (1+x\right ) \left (2-x\right ) \sin \left (x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -x \left (-x+1\right ) \left (2-x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x^{2}-x^{4}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = t^{3} \left (-x+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2}\right ) \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = t^{2} x
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2} {\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+p x = q
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = k y
\] |
✓ |
✓ |
|
\[
{}i^{\prime } = p \left (t \right ) i
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \lambda x
\] |
✓ |
✓ |
|
\[
{}m v^{\prime } = -m g +k v^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = k x-x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -x \left (k^{2}+x^{2}\right )
\] |
✓ |
✗ |
|
\[
{}y^{\prime }+\frac {y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+t x = 4 t
\] |
✓ |
✓ |
|
\[
{}z^{\prime } = z \tan \left (y \right )+\sin \left (y \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+{\mathrm e}^{-x} y = 1
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+x \tanh \left (t \right ) = 3
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y \cot \left (x \right ) = 5
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+5 x = t
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+\left (a +\frac {1}{t}\right ) x = b
\] |
✓ |
✓ |
|
\[
{}T^{\prime } = -k \left (T-\mu -a \cos \left (\omega \left (t -\phi \right )\right )\right )
\] |
✓ |
✓ |
|
\[
{}2 x y-\sec \left (x \right )^{2}+\left (x^{2}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y \,{\mathrm e}^{x}+x \,{\mathrm e}^{x} y+\left (x \,{\mathrm e}^{x}+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x \cos \left (y\right )+\cos \left (x \right )\right ) y^{\prime }+\sin \left (y\right )-y \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )+y+\left ({\mathrm e}^{x} \cos \left (y\right )+x +{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{-y} \sec \left (x \right )+2 \cos \left (x \right )-{\mathrm e}^{-y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}V^{\prime }\left (x \right )+2 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (\frac {1}{y}-a \right ) y^{\prime }+\frac {2}{x}-b = 0
\] |
✓ |
✓ |
|
\[
{}x y+y^{2}+x^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {x^{2}+t \sqrt {t^{2}+x^{2}}}{t x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = k x-x^{2}
\] |
✓ |
✓ |
|
\[
{}\tan \left (y\right )-\cot \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}12 x +6 y-9+\left (5 x +2 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x^{3}
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = x^{2} y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+3 x = {\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y \sin \left (x \right )+y^{\prime } \cos \left (x \right ) = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -y}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x+\sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x \left (\ln \left (x \right )-\ln \left (y\right )\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = {\mathrm e}^{\frac {x}{t}}+\frac {x}{t}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {1}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x +y^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y-x -4}{2 x -y+5}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{1+x}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}+x^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x +2 y-1+\left (x +y-2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x -5 y\right )^{{1}/{3}}+2
\] |
✓ |
✓ |
|
\[
{}y \left (x -y\right )-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+5 x = 10 t +2
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {x}{t}+\frac {x^{2}}{t^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x -4 y-2}{3 x -4 y-3}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }-x \cot \left (t \right ) = 4 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {3 y}{x}+y^{2} x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-y+\left (x^{2} y^{2}+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{2}-x +2 y \left (y^{2}-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x -y\right )-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y-3}{y-x +1}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y^{2} \ln \left (x \right )+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+2 x y-\cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (4 y+2 x +3\right ) y^{\prime }-2 y-x -1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}-x \right ) y^{\prime }-y+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}-x^{2}\right ) y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{2} y^{\prime } x +y^{3}-2 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \,{\mathrm e}^{x +y} \left (x^{2}+1\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x y\right )
\] |
✗ |
✗ |
|
\[
{}x \left ({\mathrm e}^{y}+4\right ) = {\mathrm e}^{x +y} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t \ln \left (y^{2 t}\right )+t^{2}
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{y^{2}-x}
\] |
✓ |
✓ |
|